Quality of couple relationship and associated factors in parents of NICU-cared infants during the first year after birth - Persson, Christine; Ericson, Jenny; Eriksson, Mats; Salari, Raziye; Flacking, Renée (Journal of Perinatology, 2024)
Objective: To describe factors associated with quality of couple relationships among parents of infants cared for in neonatal intensive care units (NICUs) 1 year after birth and examine the trajectory of the relationship quality compared to parents from maternity units (MUs). Study design: Longitudinally comparative cohort design. Parents answered surveys during the first year after discharge about the couple relationship, social support, and depressive symptoms. Results: Better social support and a hospital stay of 7–14 days were positively associated with the couple relationship in NICU mothers, whereas not having slept together with the partner and infant during hospitalization were negatively associated. Depressive symptoms were negatively associated with the relationship among NICU fathers. There were no differences in trajectory of the relationship quality between NICU and MU parents. Conclusion: To strengthen couple relationships, it could be important to improve social support, facilitate space and time for support, and enable togetherness during hospitalization.
CRIS-Team Scopus Importer:2024-12-13